Towards the first antibody-free serum biomarker assay for NAFLD - Gangadharan, B; Kumar, A; Cobbold, J; Thursz, M; Dwek, RA; Zitzmann, N (OMICS International, 2017)
Liver biopsy is the reference standard for NAFLD diagnosis and staging. NAFLD can be assessed less invasively using immunoassays to detect serum biomarkers. However, biomarkers can degrade due to sample storage conditions and therefore may not be detected using these antibody-based assays. Detection of biomarkers by mass spectrometry (MS) overcomes this disadvantage.